MILITARY EXPERTISE IN CRIMINAL PROCEEDINGS (Bulletin of criminological association of Ukraine, 2024)
In the article it has been stated that during the pre-trial investigation of military crimes, the investigator is faced with the need to establish the circumstances, which, in turn, require knowledge of many aspects of the regulation of military service and the specifics of such service. It has been established that during the investigation of military crimes in order to establish the circumstances of the use and actions of military formations, compliance of theactions (inaction) of officials with the requirements of the governing documents, special knowledge is used in the form of engaging an expert to conduct a military examination. It has been found that the Scientific and Methodological Recommendations on the Preparation and Appointment of Forensic Examinations and Expert Studies do not define and specify the object of military examination. The task of military expertise has been given. It has been indicated that the list of issues to be resolved during the military examination is determined in each specific criminal proceeding, taking into account the available initial data, the tactical tasks of the investigation, and an approximate list of issues to be resolved during the specified examination. It has been emphasized that military expertise is a relatively new type of forensic expertise. It has been noted that, in this connection, the scientific and methodological provision of military expertise is insufficient. It has been emphasized that in order to improve the scientific and methodological support of military expertise and the methodology of its conduct, it is necessary to improve the level of regulatory and legal regulation of forensic expert activity in this area.
Keywords: military crimes; special knowledge; forms of use; involvement of an expert; military expertise